The Existence of Mandailing-Language Preaching as an Instrument for Strengthening Islamic Cultural Identity in Tamiang Village, Mandailing Natal Regency - Safitriani, Safitriani; Abdullah, Abdullah (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2026)
This study examines the existence of Mandailing-language preaching as an instrument for strengthening Islamic cultural identity in Tamiang Village, Kotanopan District, Mandailing Natal Regency. Language plays an important role in religious communication because it functions not only as a medium for conveying religious messages but also as a means of transmitting cultural and religious values in society. The use of local languages in da'wah activities is considered capable of strengthening emotional relationships between preachers and the congregation so that the message of Islam can be understood more easily. This research uses a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving religious leaders, community leaders, and members of the congregation. The results show that Mandailing-language preaching still exists in several religious activities such as Friday sermons, religious lectures, recitations, and funeral gatherings. The use of Mandailing language makes religious messages feel closer to the community because it is the mother tongue used in everyday communication. However, the existence of Mandailing-language preaching currently faces challenges due to the influence of modernization and the increasing use of Indonesian among younger generations. Therefore, efforts are needed from religious leaders and the community to maintain the use of Mandailing language in religious preaching so that the Islamic cultural identity of the Mandailing community can continue to be preserved. Penelitian ini bertujuan untuk mengkaji eksistensi dakwah berbahasa Mandailing sebagai instrumen penguatan identitas budaya Islam di Kelurahan Tamiang, Kecamatan Kotanopan, Kabupaten Mandailing Natal. Bahasa memiliki peran penting dalam komunikasi keagamaan karena tidak hanya berfungsi sebagai alat penyampaian pesan, tetapi juga sebagai sarana pewarisan nilai-nilai budaya dan keagamaan dalam masyarakat. Penggunaan bahasa daerah dalam kegiatan dakwah dapat memperkuat kedekatan emosional antara dai dan jamaah sehingga pesan dakwah lebih mudah dipahami. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi dengan melibatkan tokoh agama, tokoh masyarakat, serta jamaah. Hasil penelitian menunjukkan bahwa dakwah berbahasa Mandailing masih digunakan dalam berbagai kegiatan keagamaan seperti khutbah Jumat, pengajian, ceramah, dan kegiatan takziah. Bahasa Mandailing membuat pesan keagamaan terasa lebih dekat dengan kehidupan masyarakat karena merupakan bahasa sehari-hari yang digunakan dalam interaksi sosial. Namun demikian, eksistensi dakwah berbahasa Mandailing menghadapi tantangan akibat modernisasi dan meningkatnya penggunaan bahasa Indonesia di kalangan generasi muda. Oleh karena itu diperlukan strategi dari tokoh agama serta dukungan masyarakat untuk mempertahankan penggunaan bahasa Mandailing dalam kegiatan dakwah agar identitas budaya Islam masyarakat Mandailing tetap terjaga.